Comparative Analyses of Clearing Efficacies of Tissue Clearing Protocols by Using a Punching Assisted Clarity Analysis - Woo, Jiwon; Lee, Eunice Yoojin; Lee, Mirae; Ku, Seockmo; Park, Jeong-Yoon; Cho, Yong Eun (Frontiers in Bioengineering and Biotechnology, 2022)
The advent of tissue clearing methods, in conjunction with novel high-resolution imaging techniques, has enabled the visualization of three-dimensional structures with unprecedented depth and detail. Although a variety of clearing protocols have been developed, little has been done to quantify their efficacies in a systematic, reproducible fashion. Here, we present two simple assays, Punching-Assisted Clarity Analysis (PACA)-Light and PACA-Glow, which use easily accessible spectroscopy and gel documentation systems to quantify the transparency of multiple cleared tissues simultaneously. We demonstrate the use of PACA-Light and PACA-Glow to compare twenty-eight tissue clearing protocols on rodent brains. We also show that regional differences exist in tissue transparency in the rodent brain, with cerebellar tissue consistently achieving lower clearing levels compared to the prefrontal or cerebral cortex across all protocols. This represents the largest comparative study of tissue clearing protocols to date, made possible by the high-throughput nature of our PACA platforms.